2008
DOI: 10.1196/annals.1427.021
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria and Hypoxia‐induced Gene Expression Mediated by Hypoxia‐inducible Factors

Abstract: The influence of mitochondrial activity on gene expression programs, particularly those involved in neuroprotection and repair, is likely to play an important role in the pathophysiology of neurodegenerative diseases. One such gene expression program is activated by the cellular pathway that senses a decrease in optimal oxygen levels and leads to activation of a family of transcriptional activators called hypoxia-inducible factors (HIFs). HIFs are members of the bHLH-PAS family of transcription factors and are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…Some researchers have found that IH training can affect many nuclear transcription regulators, such as hypoxiainducible transcription factors (HIFs) (Chavez et al 2008;Zhao et al 2008), Janus kinase/signal transducer and activator of transcription factor(JAK/STAT) (Volgin and Kubin 2006) and c-fos (Nanduri et al 2008), to activate cell signal transduction pathways. HIFs activate the expression of more than a 100 proteins that regulate cell metabolism, survival, angiogenesis, vascular tone, hematopoiesis and other functions (Manalo et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have found that IH training can affect many nuclear transcription regulators, such as hypoxiainducible transcription factors (HIFs) (Chavez et al 2008;Zhao et al 2008), Janus kinase/signal transducer and activator of transcription factor(JAK/STAT) (Volgin and Kubin 2006) and c-fos (Nanduri et al 2008), to activate cell signal transduction pathways. HIFs activate the expression of more than a 100 proteins that regulate cell metabolism, survival, angiogenesis, vascular tone, hematopoiesis and other functions (Manalo et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…[124][125][126][127][128] ROS, through the regulation of hypoxia-inducible factor-1, are also important in O 2 sensing, 125 which is essential for maintaining normal O 2 homeostasis. In pathological conditions ROS are involved in inflammation, endothelial dysfunction, cell proliferation, migration and activation, extracellular matrix deposition, fibrosis, angiogenesis and vascular remodeling [129][130][131] ( Figure 3). …”
Section: Ros and Vascular Biology In Hypertensionmentioning
confidence: 99%
“…In accordance with this assumption, the present data indicated that mitoK ATP channel opening participates in the chronic proliferation of hPASMCs in collaboration with HIF-1α under hypoxic conditions. miR-210, which is upregulated by HIF-1α, is considered to be among the most hypoxia-sensitive miRs and a microregulator of the hypoxia pathway (34). As a downstream target of miR-210 (12,33,35), ISCU is responsible for the assembly of iron sulfur clusters [Fe-S] in mitochondrial respiratory complexes (complexes I, II and III) (21,36).…”
Section: Discussionmentioning
confidence: 99%